The Impact of 5G on Business Models for Mobile Operators in Emerging Markets - Banda, Laurence; Feukeu, Etienne Alain (Journal of Telecommunications and the Digital Economy, 2025)
The advent of 5G wireless technologies has created new opportunities and challenges for mobile operators in emerging markets. However, the disruptive nature of 5G networks is likely to transform existing value chains and impact the current mobile operator-centric ecosystem, rendering traditional business models inadequate. The introduction of 5G networks therefore requires the adoption of new business models or the reconfiguration of existing ones to ensure that mobile operators can achieve both economic value and technological innovation in a sustainable way. This study investigates the factors that impact business models of mobile operators in emerging markets as a result of 5G deployment. The study was conducted using the qualitative research method by adopting an interpretivist research philosophy. Primary data was collected inductively through a case study approach with 10 semi-structured online interviews conducted in 8 emerging markets in the Sub-Saharan Africa region. The results show that when 5G is commercially deployed, several aspects, including internal, external and hybrid factors impact the business models of mobile operators.